systems of equations

Mathematics
Tutor: None Selected Time limit: 1 Day

3x-y=8

3x=4-y

May 20th, 2015

3x-y=8

Therefore, y = 3x - 8

Substitute into second equation

3x = 4 - (3x - 8)

3x = 4 - 3x + 8

6x = 12

x = 2

y = 3(2) - 8

y = -2

May 20th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
May 20th, 2015
...
May 20th, 2015
Dec 10th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer